Lateral thoracotomy by vertical incision - Bergalli, Luis; Carriquiry, Luis; Piacenza, Guillermo; Mesa, Guillermo; Rinaldi, Bruno; Pradines, Jorge C (Cirugía del Uruguay, 1980)
On the basis of 10 cases, the authors report on the technique, indications and contraindications which, in their opinion, should apply to a lateral thoracotomy by vertical incision. Becausse of the excellent respiratory functionality of patients who have undergone this operation, the fact that it is relatively painless, its ample field and the esthetic iactor